Poverty and precarity in Portugal: a multidimensional approach - Carvalho, Izaura Solipa Figueira Pires de (2016)
This research assesses poverty levels in Portugal within a multidimensional approach, over a period from 2008 to 2014. Further, it aims at inferring a causal relationship between precarious jobs and the estimated multidimensional poverty level. This research adds to the existing literature by applying a discrete choice experiment in the construction of the poverty index, as well as by nding causality between poverty and precarity. Empirical results suggest that, while multidimensional poverty levels are higher than the European Union poverty statistics, computed with relative income, precarity has a negative impact on the individual s wellbeing.